Characterization of the complete plastome of Delphinium montanum, a polyploid, endemic and endangered Pyrenean Larkspur - Pascaline Salvado; Christel Llauro; Marie-Christine Carpentier; Valérie Delorme-Hinoux; Joris A. M. Bertrand (Mitochondrial DNA. Part B. Resources, 2022)
Delphinium montanum DC. 1815, is an endangered larkspur endemic to the Eastern Pyrenees. For biogeographic and conservation purpose, a hybrid assembly approach based on long- and short-read genomic data allowed us to successfully assemble whole plastid genome of Delphinium montanum. The complete plastome is 154,185 bp in length, consisting of a pair of inverted repeats (IRs) of 26,559 bp, a large single-copy (LSC) region and a small single-copy region (SSC) of 84,746 and 16,320 bp, respectively. It was found to contain 136 genes, including 84 protein-coding genes, 44 trRNA genes and 8 rRNA genes. The overall GC content of the plastid genome is 38.3%. Phylogenetic inference supports the polyphyly of the Delphinium genus.